Values and Informal Education: From Indigenous Africa to 21st Century Vermillion - Mejai B.M. Avoseh (Adult Education Research Conference, 2008)
Values cut through every human activity and are integral to human existence because human beings are ‘valuing animals’. Values motivate most adults to engage in any learning activity. Values in informal education are foundations for lifelong learning as a basis for participatory democracy, equity and social justice. This paper uses literature to do a conceptual analysis of values and informal education as imperatives for participatory democracy and social justice.
Keywords: African; indigenous; informal; lifelong; social justice; values